A Study of Flow in Entrepreneurs - Woodruff, Timothy James (2015)
What is the experience of flow like in Entrepreneurs? This work defines the concept of an entrepreneur, discusses that concept in regards to creativity, and accesses the impact Flow has on entrepreneurial behaviour. Within entrepreneurship theory and cognitive theories of creativity extensive research has been performed. However, the experience of entrepreneurship itself has had no such treatment. Most authors recognise the role that creativity plays in entrepreneurship, and, within that claim theories often hold that intrinsic motivation plays a large role. The experience of ‘Flow’ (Csikszentmihalyi, 1996) is observed in other domains as playing a large role in creativity and the standard of performance (e.g., Jackson et al., 1998; Jackson, 1992; Stavrou et al., 2007). This exploratory study, through qualitative interviews, attempts to provide insights into the relationship between flow and the entrepreneur in order to make suggestions for future theory development.